INTERNALISASI NILAI NASIONALISME MELALUI PEMBELAJARAN KE-NU-AN PADA SISWA KELAS VIII DI MTs TARBIYATUL MUBTADIIN WILALUNG DEMAK TAHUN 2022 - Siti Zulfah; Ruwandi Ruwandi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2023)
Internalization of Nationalism through NU learning is considered capable of having a good impact on students, schools and the community by creating a nationalist environment. This research method uses a field approach which is descriptive qualitative in nature involving resource persons from the Madrasah Head, Curriculum, Teachers, and students. Data collection was obtained through observation, interviews, and document studies. The results of this study found that: 1) Internalization steps include planning, implementing and evaluating by formulating core competencies and basic competencies, formulating competency achievement indicators, formulating learning objectives, selecting learning materials, selecting learning methods, determining learning steps, choose the media or learning resources, determine the evaluation of learning. 2) The difficulties in the internalization process include: Difficulties in formulating competency achievement indicators, difficulties in choosing learning methods, limitations of learning media, difficulties in implementing learning evaluations. 3) The solution to internalizing the value of Nationalism through NU-ness learning includes: Being active in Subject Teacher Consultations (MGMP) activities, participating in teacher training, creating active learning. The implication of this research is that the internalization of nationalism values ​​can be increased through the implementation of NU-ness learning activities.